Synthesis of Fluorescent 2,6-Dicyano-3,5-Disubstituted Anilines Using Cellulose Sulfuric Acid in Aqueous Media - Zonouzi, A.; Izakian, Z.; Abdi, K.; Ng, S.W. (John Wiley & Sons, 2016)
The synthesis of some fluorescent 2,6-dicyano-3,5-disubstituted anilines using cellulose sulfuric acid (Cellulose-SA) as an environmentally benign catalyst in H2O is described. The one-pot reaction of 1,3-diketone and three equiv. of malononitrile was carried out in the presence of one equiv. of a secondary amine, Cellulose-SA as catalyst, and H2O as solvent. The photophysical properties (λAbs., λFlu.) of the synthesized compounds in CH2Cl2, MeCN, and MeOH have been measured. The emission spectra of the new compounds in the solid state are also reported.